The Use of Qual2KW to Analyze the Concentration of pH, Nitrate, Phosphate, and Fecal Coliform on Water Quality: A Case Study of the Klampok River, Semarang Regency - Winardi Dwi Nugraha; Sudharto Prawata Hadi; Setia Budi Sasongko; Adranandini Noor Anisa; Mochamad Arief Budihardjo (Universitas Diponegoro, 2022)
Usually, the main source of water is a river, which makes it essential to ensure that the water from that source is not polluted and in accordance with the water quality standards. Water quality can deteriorate as a result of domestic and industrial waste. This quality is measured based on several parameters, such as the concentration of pH, nitrate, phosphate, and fecal coliform in the water. QUAL2KW can be used to analyze river water quality in order to solve several water quality-related problems. The main river water source in Semarang Regency is the Klampok River, whose water is used to support agriculture, livestock, and other activities. This study aims to determine the concentration of the above-mentioned parameters in the samples from the Klampok River using QUAL2KW. The water samples are obtained from different six points on the Klampok River, and the chi-square test is used for validation. From the laboratory test results for the river-quality parameters, after being simulated using QUAL2KW and validated using the chi-square method, it can be concluded that the quality of the Klampok River belongs to class II. These results can be used as a reference by the Semarang Regency government in managing river water quality.